Acidic tumor microenvironment-sensitive liposomes enhance colorectal cancer therapy by acting on both tumor cells and cancer-associated fibroblasts. Issue 23 (7th June 2021) - Li, Chenglei; Li, Zhaohuan; Gong, Xue; Liu, Jianhao; Zheng, Tingyue; Wang, Fangqing; Wu, Jingliang; Zhang, Bo
Abstract : IRI&398-s-LPs was destroyed in the TME, leading to rapid release of drugs, thus killing tumor cells and CAFs simultaneously. The combinational strategy by eliminating both "seeds" and "soil" of the tumor is beneficial for enhancing antitumor effect. Abstract : Cancer-associated fibroblasts (CAFs) play a crucial role in facilitating tumor invasion and metastasis, which act as the "soil" in the tumor microenvironment (TME). Accordingly, it would be a promising strategy to enhance the antitumor effect by killing both tumor cells and CAFs simultaneously. Herein, novel TME acid-responsive liposomes for co-delivery of IRI and 398 (IRI&398-s-LPs) were developed, in which the rapid release of both drugs could be triggered under acidic conditions. Notably, a CT-26/3T3 cell co-culture system was used to mimic the real TME both in vitro and in vivo . Cellular immunofluorescence revealed that IRI&398-s-LPs could efficiently decrease the activation of CAFs. In vitro cytotoxicity evaluation demonstrated that IRI&398-s-LPs exhibited higher cytotoxicity than the other liposomal formulations in the CT-26 and CT-26/3T3 cell co-culture system. In vivo NIRF imaging showed that the IRI&398-s-LPs could increase drug accumulation in the tumor sites. Furthermore, IRI&398-s-LPs not only presented superior in vivo anti-tumor activity in CT-26 bearing BALB/c mice, but also enhanced the effect in CT-26/3T3 cell bearing mice with decreased collagen and CAF biomarker expression. Furthermore, IRI&398-s-LPs also presented superior anti-metastatic efficiency in a lung metastasis model. These results indicated that this combinational strategy for eliminating both tumor cells and CAFs provides a new approach for cancer therapy, and the prepared TME-responsive liposomes for co-delivery of drugs hold promising clinical application prospects.